Pengaruh Layanan Penguasaan Konten Teknik Mind Mapping Terhadap Motivasi Belajar Siswa - Amalia, Rizki Umu (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this research is to know the learning motivation of students before and after the given mastery of content service mind mapping techniques and whether the mastery of content service mind mapping techniques effect on learning motivation of students. This research is experimental research design used is one group pretest-posttest design. Pre and post test form learning motivation scale. The population is all of the 5th grade the amount of 37 students and sample using a sampling of saturated so that the number of subjects for research are all students of 5th grade. Test hypotheses using a t-test analysis test by comparing the results of a pretest and posttest, obtained result tcount = 10.465 > ttable = 2.021, which means Ha accepted and Ho rejected. The result showed that the learning motivation of students before and after the given mastery of content service mind mapping techniques experience an increase of 9.23%.